Traditsija i inovatsii vo Makedonskite tsrkovnoslovenski knijevni spomenitsi od turskiot period = Tradition and innovations in the Macedonian churchslavonic literary monuments from the Turkish period. - İlievski, Petar Khr. (Skopje)
393 s.